Native English teachers’ beliefs and practices in teaching oral communication: A multiple case study in China - Lan Wang; Ricky Lam (Indonesian Journal of Applied Linguistics, 2023)
Although previous studies in the education field have investigated how teachers’ beliefs and practices converge or diverge, native English teachers’ (NETs) beliefs and practices remain underrepresented and underexplored, particularly with respect to university-level English speaking instruction in the Chinese context. This qualitative study used interviews and classroom observations over one semester to examine the pedagogical beliefs and actual classroom practices of three NETs instructing a course in oral communication with English as a foreign language (EFL). Based on the data analysis, this multiple case study found that the three native EFL teachers’ practices converged with their beliefs related to language, teaching, and teachers’ roles. However, divergences existed in terms of teaching and student learning. Teachers’ personal, learner-related, and contextual factors modified teachers’ practices and affected their decisions in putting their beliefs into practice. The results imply that it is essential for NETs to engage in critical reflection and enhance their professional agency, which helps them make appropriate classroom decisions to achieve resonance between their beliefs and practices. University administrators in the Chinese context may consider creating a more conducive environment for teacher training, increasing NETs’ sense of belonging, and further facilitating teachers’ professional development.